Implementation of Peresean Game as a Medium to Enhance Sasak Cultural Appreciation Among Young Generation - Hamzan Ahmadi; Aris Sudianto; Hariman Bahtiar (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2026)
Peresean is a traditional custom of the Lombok Sasak Tribe, which is armed with rattan (jalin), using a shield (ende) made from cow skin and when the peresean event takes place it will be accompanied by the typical music of the Lombok Sasak Tribe, namely gendang beleq. The clothing worn by peresean participants (pepadu) is a headband (sapuq), sarong (selewoq), cloth belt (bebet) and bare chest. The peresean culture is now starting to be held less frequently and is not very popular with Lombok youth in particular. This is because today's youth prefer digital games that are more varied and do not require a lot of stamina. So from there it became a reference for making a fighting type peresean game using the GDLC method as a means to preserve the Sasak tribe's peresean culture. adjust regulations according to the target audience. The final result of this production is a fighting game that runs on a PC (personal computer), and is targeted at all ages. The features that have been designed have fulfilled what was desired. In this fighting type research game, there is information and moral messages about preserving local culture. It is hoped that this peresean game application can become a medium of introduction and education for the wider community, especially the people of Lombok, about the peresean culture of the Lombok Sasak Tribe.